2018
DOI: 10.1007/s00280-018-3634-4
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of panobinostat in pediatric patients with refractory solid tumors, including CNS tumors

Abstract: A significant biological effect of panobinostat, measured by acetylation status of histone H3 and H4, was achieved at a dose of 15 mg/m. PK data and drug tolerability at 15 mg/m was similar to that previously published.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…Other standard of care drugs were not eligible (e.g., topotecan and doxorubicin) as the EC50s were too high to be achieved in vivo. Six drugs of the HDAC inhibitor group were active against HPG-RBG1 ( Figure 5), but only panobinostat was selected for further synergistic evaluations as it has already been tested as part of combination treatments in preclinical models of pediatric tumors and published pharmacokinetic data supports that the EC50 (67.2 nM) would be clinically attainable [17][18][19][20].…”
Section: In Vitro and In Vivo Pharmacological Sensitivitymentioning
confidence: 99%
“…Other standard of care drugs were not eligible (e.g., topotecan and doxorubicin) as the EC50s were too high to be achieved in vivo. Six drugs of the HDAC inhibitor group were active against HPG-RBG1 ( Figure 5), but only panobinostat was selected for further synergistic evaluations as it has already been tested as part of combination treatments in preclinical models of pediatric tumors and published pharmacokinetic data supports that the EC50 (67.2 nM) would be clinically attainable [17][18][19][20].…”
Section: In Vitro and In Vivo Pharmacological Sensitivitymentioning
confidence: 99%
“…HDAC inhibitors have been evaluated in clinical trials for adults with sarcomas and have demonstrated limited success as monotherapy [82]. In pediatrics, HDAC inhibitors have been evaluated as single agents in phase 1 clinical trials which included patients with RMS and while these agents were well tolerated, there were no objective responses reported [84][85][86][87][88]. These agents may be more effective in combination with chemotherapy or other targeted agents, and there is an ongoing clinical trial for individuals with RMS aged 16 years and older studying the HDAC inhibitor mocetinostat in combination with vinorelbine (NCT04299113).…”
Section: Histone Deacetylase Inhibitorsmentioning
confidence: 99%
“…Wood et al that was performed in pediatric patients with solid tumor, panobinostat was used as 10 mg dose which was well tolerated by pediatric patients. 17 We used etoposide and doxorubicin as the concomitant chemotherapy regimen in order to prevent multidrug resistance. Additionally, the study of Guan Wang et al on neuroblastoma cells revealed that panobinostat increases the cytotoxic effects of doxorubicin or etoposide on high-risk neuroblastoma cells.…”
Section: Case Presentationmentioning
confidence: 99%